2023
DOI: 10.3390/app131910555
|View full text |Cite
|
Sign up to set email alerts
|

Apical Transportation of Apical Foramen by Different NiTi Alloy Systems: A Systematic Review

Francesco Puleio,
Ugo Bellezza,
Alessandra Torre
et al.

Abstract: Endodontic shaping can lead to canal and apical anatomical alterations, which may compromise the outcome of root canal treatment. The objective of this systematic literature review is to assess whether the use of martensitic endodontic instruments can result in less apical transportation compared to austenitic instruments during endodontic therapy. A search was conducted on PubMed, Ovid MEDLINE, and the Web of Science. The inclusion criteria were in vitro studies comparing apical transportation using endodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Studies have indicated that apical enlargement beyond size 35/.04 improves smear layer removal at the apical third using syringe and needle irrigation [ 46 ]. The optimal size for apical preparation remains a subject of debate, with larger apical preparations associated with an increased risk of iatrogenic errors, including root canal transportation, zipping, or perforation [ 47 ]. In line with Haupt et al [ 23 ], preparation up to size 40/.04 was undertaken in this study to achieve a satisfactory balance between apical enlargement, cleaning efficacy, and the likelihood of procedural errors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that apical enlargement beyond size 35/.04 improves smear layer removal at the apical third using syringe and needle irrigation [ 46 ]. The optimal size for apical preparation remains a subject of debate, with larger apical preparations associated with an increased risk of iatrogenic errors, including root canal transportation, zipping, or perforation [ 47 ]. In line with Haupt et al [ 23 ], preparation up to size 40/.04 was undertaken in this study to achieve a satisfactory balance between apical enlargement, cleaning efficacy, and the likelihood of procedural errors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors considered that this could be related to the size of the last file (size #35) used to reach the working length: the reason seems to be the flatness of the apical third of the root, as well as the lower elasticity of the stainless-steel alloy compared with the nickel-titanium file, so that the prepared root canals do not maintain their original orientation. The mechanical properties of the material and the cross-sectional shape of the file might have an influence on root canal transport [11,20,21]. In addition, other factors such as the type of application, the anatomy of the root canal system and the size of the instrument can also influence root canal transport during instrumentation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the Controlled Memory Effect (controlled restoring force), the files always work in the center of the canal, which significantly reduces the risk of via falsa, canal center displacement, or canal perforation. The analysis of a systemic review showed that the use of martensitic endodontic instruments results in less apical transport during the endodontic shaping phases compared with austenitic instruments, due to the greater flexibility of martensitic instruments [11]. By using HyFlex EDM files, the number of files can be reduced to 2-3, depending on the clinical situation, especially in straight and larger canals.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide releases hydroxyl ions (OH-) at low concentrations, resulting in a significant reduction in bacterial load [ 6 ]. However, the reported risk of oxygen gas release causing emphysema and the limited tissue lytic activity of chlorhexidine restrict their use in daily endodontic practice, making NaClO and EDTA the most commonly used irrigants [ 10 , 11 , 12 ]. Current irrigation protocols involve alternating NaClO (to attack organic residues and bacteria) and EDTA (to denature the mineral component and the smear layer produced by instrumentation), with intermediate irrigation phases using saline solution [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%